Water and ethanol extracts of tamarind (Tamarindus indica) suppress lipid accumulation in 3T3-L1 cells - Kenn Rafael Harjadi; Momoko Ishida; Kosuke Nishi; Takuya Sugahara; Agus Budiawan Naro Putra (Hasanuddin University Food Science and Technology Study Program, 2022)
Obesity is one of the major health problems which could trigger the development of many other non-communicable diseases. Tamarind (Tamarindus indica) is a multi-purpose plant that provides many health benefits, including anti-obesity potentials. In Indonesia, it is often used as a traditional food component in many dishes. A recent in vivo study proved that tamarind might reduce the bodyweight of obese rats. To further investigate the anti-obesity effect of tamarind, an in vitro study using 3T3-L1 pre-adipocytes was conducted. During differentiation, 3T3-L1 cells synthesize and accumulate lipid in the form of triglycerides in the cytoplasm. Tamarind water and ethanol extracts were incorporated into the medium during the differentiation stage of the cells. Oil red O staining assay was used to measure the total lipid accumulated. Results showed that both tamarind water and ethanol extracts exhibited non-cytotoxicity effects on 3T3-L1 cells. In addition, tamarind water extract at 10 mg/mL decreased the total lipid accumulated significantly to 80.5% compared with that of control, while tamarind ethanol extract showed less lipid accumulation inhibitory effect at any doses tested. This study revealed that tamarind water extract has the potential to reduce lipid accumulation, thus showing an anti-obesity effect.